2023
DOI: 10.3233/ch-231876
|View full text |Cite
|
Sign up to set email alerts
|

A combination of ultrasound and contrast-enhanced ultrasound improves diagnostic accuracy for the differentiation of cervical tuberculous lymphadenitis from primary lymphoma

Naxiang Liu,
Yijie Chen,
Yaoqin Wang
et al.

Abstract: OBJECTIVES: To present a method combining ultrasound (US) and contrast-enhanced ultrasound (CEUS) features for differential diagnosis of cervical tuberculous lymphadenitis (CTL) and primary lymphoma. METHODS: A total of 155 patients with CTL (n = 49) and lymphoma (n = 106) who underwent US and CEUS were retrospectively included. The features extracted from US and CUES and the significant clinical data were created three models using the least absolute shrinkage and selection operator and logistic regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, health professionals often encounter challenging cases with overlapping imaging features in differentiating metastasis from lymphoma only with conventional B-mode US and even with Doppler US 14 . It has been reported that a combination of ultrasound and contrast-enhanced ultrasound has good diagnostic value in distinguishing between cervical lymphadenitis and primary lymphoma 15 . However, these methods still depend on the subjectivity of the radiologist’s judgment in ultrasound interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…However, health professionals often encounter challenging cases with overlapping imaging features in differentiating metastasis from lymphoma only with conventional B-mode US and even with Doppler US 14 . It has been reported that a combination of ultrasound and contrast-enhanced ultrasound has good diagnostic value in distinguishing between cervical lymphadenitis and primary lymphoma 15 . However, these methods still depend on the subjectivity of the radiologist’s judgment in ultrasound interpretation.…”
Section: Introductionmentioning
confidence: 99%